A strong hydroxyl-affinity heterojunction electrode material with a wide potential window and its preparation method and application

Through microwave-assisted heterojunction electrode construction design, a strongly hydroxide root-based heterojunction material is formed, which solves the complex problems of electrolyte modification measures in the prior art and the influence of electrocatalytic activity of the electrode material, and achieves a significant broadening of the potential window and increasing the energy density in conventional water electrolytes.

CN119314807BActive Publication Date: 2025-03-21GUANGDONG OCEAN UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411837474.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

When the prior art broadens the potential window of supercapacitors, electrolyte modification measures are often used, but there are problems such as high cost, complex system, unclear synthesis mechanism, larger viscosity, low ion conductivity, and safety. At the same time, the electrocatalytic activity of the electrode material decomposition has affected the energy density and is difficult to meet the application needs.

Method used

Through microwave-assisted heterojunction electrode construction design, microwave effect is used to induce the formation of strong hydroxide root heterojunction materials, which enhances the potential window. This material consists of non-priced transition metal oxides, carbon oxides, hydroxides, sulfides or lanthanide metal fluorides, and is prepared by microwave-assisted hydrothermal process to form a heterojunction electrode material with high OH-adsorption energy.

Benefits of technology

It has achieved a significant expansion of the electrode potential window in conventional water electrolytes. The stable potential window can be greater than 0.8 V and close to the water decomposition limit by 1.23 V, which significantly improves the energy density of the supercapacitor and avoids complex problems caused by electrolyte modification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314807B_ABST
    Figure CN119314807B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of materials science, nanotechnology and new energy, and specifically is a strongly hydroxyl-affinity heterojunction electrode material with a wide potential window, and a preparation method and application thereof. The heterojunction electrode material is prepared by a microwave-assisted hydrothermal process, so that the heterojunction material has strong hydroxyl-affinity; the potential window of the heterojunction electrode material is greater than 0.8V under a conventional aqueous electrolyte three-electrode test system; the heterogeneous components in the heterojunction electrode material are all transition metal inorganic compounds. The strongly hydroxyl-affinity heterojunction material of the present invention increases the electrode potential window, which can reach up to 1.2V, close to the limit of water decomposition of 1.23 V. Devices assembled with strongly hydroxyl-affinity heterojunction materials as supercapacitor electrode materials can obtain high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of material science, nanotechnology and new energy, and specifically relates to a strongly hydroxyl-affinity heterojunction electrode material with a wide potential window, and a preparation method and application thereof. Background Art

[0002] As a new type of high-efficiency energy storage device, supercapacitors have broad application prospects in many application fields. However, their low energy density limits their commercial application. According to the energy density calculation formula E=1 / 2CV 2It can be seen that the energy density is proportional to the square of the potential window, and the energy density of supercapacitors can be significantly improved by widening the potential window. At present, the widening of the potential window is generally achieved by electrolyte modification measures, such as salt-soluble electrolyte "salt-in-water", introduction of redox electrolyte pairs, and adjustment of pH value. The current existing technologies, such as: Patent CN202311246540.3 "An ionic liquid electrolyte with a wide window, its preparation method and application", CN202310191143.4 "A zwitterionic hydrogel electrolyte, its preparation method and application", CN202211634786.3 "A method for constructing a zinc ion flexible hybrid supercapacitor with a wide voltage window", CN202210937540.7 "A wide voltage window aqueous electrolyte for forming SEI film based on physical process, its preparation method and application", CN 202111543295.3 "A low-temperature and high-voltage resistant aqueous electrolyte, its preparation method and application in micro supercapacitors", etc., all obtain a wide potential window from the perspective of the electrolyte. In addition, for example, patent CN202210766942.5 "Preparation and Application of Conductive Polymer-Dihydrate Tungsten Trioxide / Tungsten Self-Supporting Electrode with Wide Voltage Window" seems to involve the construction of a multi-component composite electrode material to obtain a wide potential window, but its essence is still electrolyte modification, and its electrolyte is a mixed organic aqueous solution of modified hydrochloric acid, hydrogen peroxide and aniline, rather than a traditional aqueous electrolyte. In addition, the "wide potential window" described in the currently reported patents such as patent CN 202110861587.5 "Preparation of an Al-doped MnO2 electrode material and construction of a flexible superelectric device with a wide voltage window" is actually the voltage of the assembled integrated supercapacitor device as a whole, that is, by assembling an asymmetric supercapacitor, a wide potential window is obtained, which is actually the sum of the voltage differences between the positive and negative electrodes in the two-electrode system. Compared with conventional aqueous electrolytes, such as ordinary neutral (such as Na2SO4) or alkaline (such as KOH), the above-mentioned electrolyte modification and optimization measures face problems such as high cost, complex system, unclear synthesis mechanism, increased viscosity, low ion conductivity, and safety. At the same time, the above-mentioned measures to construct asymmetric supercapacitors are limited by the influence of the electrocatalytic activity of water decomposition of electrode materials, resulting in energy density that is difficult to meet application requirements. Based on the above analysis, it is urgent to develop an electrode material system with a wide potential window suitable for conventional aqueous electrolytes from the perspective of electrode material modification design.

[0003] In addition, the articles that have been reported to obtain a wide potential window from the perspective of electrode material design, such as "Microwave-assisted in-situ isomorphism via introduction of Mn into CoCo2O4forbattery-supercapacitor hybrid electrode material" (Chemical Engineering Journal 430 (2022) 132729), "Tunable stable operating potential window forhigh-voltage aqueous supercapacitors" (Nano Energy 63 (2019) 103848), "Structure reinforced birnessite with an extended potential window forsupercapacitors" (J. Mater. Chem. A, 2020,8, 8969-8978), etc., are essentially to use doping engineering to optimize the chemical composition and component ratio of single-component electrode materials to change the electrochemical properties, thereby obtaining a wide potential window. Although the above work significantly improves the potential window of electrode materials from the perspective of electrode material modification. However, the controllability of the doping effect in the above work and the influence of doping on the material structure may cause the mechanical strength and structural stability of the material to decrease, resulting in expansion, contraction or cracking of the material during long-cycle charging and discharging, affecting the cycle life.

[0004] Therefore, from the perspective of electrode material design, how to develop an electrode material system and related preparation methods with a wide potential window suitable for conventional aqueous electrolytes while ensuring that other electrochemical indicators of the electrode material are not affected is the key and difficulty in this field. Summary of the invention

[0005] Different from the conventional electrolyte modification to broaden the stable electrochemical window of the electrode, the present invention is a microwave-assisted heterojunction electrode construction design. From the perspective of electrode material design, the microwave effect is used to induce the formation of heterojunction materials, which produces strong hydroxyl affinity and effectively improves the potential window. Strong hydroxyl affinity is similar to the concepts of lithium affinity, lithium phobia, zinc affinity, and zinc phobia in lithium batteries and zinc batteries. Its characteristics are: in a conventional aqueous electrolyte system, the heterojunction material of the present invention has a high OH -Adsorption energy is strong hydroxyl affinity. Strong hydroxyl affinity heterojunction materials can adsorb and store a large amount of electrolyte ions, change the local microstructure of the electrode-electrolyte interface, and thus make the gas molecules such as OH near the electrode material-electrolyte surface - , H + , it is difficult to be further adsorbed and undergo conversion gasification reaction, which can increase the overpotential of OER and HER, inhibit the occurrence of water decomposition reaction, and thus widen the potential window, that is, from the perspective of electrode material design, achieve the widening of the electrode potential window. That is, the present invention designs and prepares a strong hydroxyl-philic supercapacitor heterojunction electrode material, utilizes its strong adsorption and storage capacity for electrolyte ions, inhibits the gasification reaction process, and achieves the purpose of improving the electrode electrochemical window.

[0006] The present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a strongly hydroxyl-affinity heterojunction electrode material with a wide potential window. The heterojunction electrode material is prepared by a microwave-assisted hydrothermal process so that the heterojunction material has a strong hydroxyl-affinity; the potential window of the heterojunction electrode material is greater than 0.8V under a conventional aqueous electrolyte three-electrode test system; the heterogeneous components in the heterojunction electrode material are all transition metal inorganic compounds.

[0008] In the above technical solution, further, the heterojunction electrode material is composited by two heterogeneous components, both of which are transition metal inorganic compounds; the transition metal inorganic compound is a non-precious transition metal oxide, carbon oxide, hydroxide, sulfide or lanthanide metal fluoride.

[0009] In the above technical scheme, further, the non-precious transition metal oxides include CuO, Fe3O4, Co3O4 or NiMn2O4; the non-precious transition metal carbon oxides include MnCO3; the non-precious transition metal hydroxides include layered double hydroxides (LDH), preferably NiMn LDH, CoAl LDH; the non-precious transition metal sulfides include CuS, MoS2; and the lanthanide metal fluorides include LaF3.

[0010] In the above technical solution, further, the heterojunction electrode material is formed by combining any two of the above transition metal inorganic compounds under microwave assistance, such as CoCo2O4@NiMn2O4, MnCO3 / NiO or Co3O4 / LaF3.

[0011] In the above technical solution, further, the heterojunction electrode material can improve the potential window, and its stable potential window under the conventional aqueous electrolyte three-electrode test system is greater than the 0.8V limit of conventional transition metal inorganic compounds, and can be close to the limit of water decomposition 1.23 V. The conventional aqueous electrolyte three-electrode test system is: the synthesized material is the working electrode, the platinum mesh is the counter electrode, the saturated calomel electrode is the reference electrode, and the electrolyte is a conventional neutral or alkaline electrolyte, such as neutral Na2SO4, alkaline KOH.

[0012] In the above technical solution, further, the OH of the heterojunction material - Adsorption energy <-3eV, with high hydroxide affinity.

[0013] In the above technical solution, further, the microwave-assisted hydrothermal process includes: treating the raw material solution of heterogeneous components with microwaves, the microwave power is 800-1100 W, the temperature is raised to 120-150° C., and the microwave treatment time is 1-3 hours.

[0014] In the above technical solution, further, before the microwave heating temperature reaches 100°C, it is heated at a rate of 10~12°C / min, after heating to 100°C, it is kept warm for 5 min, and then reaches the target temperature at 5~8°C / min.

[0015] The second aspect of the present invention provides a method for making an electrode material have a wide potential window, wherein the method uses a microwave-assisted hydrothermal process to prepare a heterojunction electrode material, so that the heterojunction electrode material has strong hydroxyl affinity, OH - Adsorption energy <-3eV.

[0016] In the above technical scheme, further, the heterojunction electrode material is a composite of two heterogeneous components of non-precious transition metal oxides, carbon oxides, hydroxides, sulfides or lanthanide metal fluorides; the microwave-assisted hydrothermal process includes: the raw material solution of the heterogeneous components is treated with microwaves, the microwave power is 800-1100 W, the temperature is raised to 120-150°C, and the microwave treatment time is 1-3h; before the microwave heating temperature reaches 100°C, it is heated at a rate of 10-12°C / min, after heating to 100°C, it is kept warm for 5 min, and then the target temperature is reached at 5-8°C / min; the non-precious transition metal oxides include CuO, Fe3O4, Co3O4 or NiMn2O4; the non-precious transition metal carbon oxides include MnCO3; the non-precious transition metal hydroxides include layered double hydroxides (LDH), preferably NiMn LDH, CoAl LDH; the non-precious transition metal sulfides include CuS and MoS2; the lanthanide metal fluorides include LaF3.

[0017] The third aspect of the present invention provides the application of the aforementioned heterojunction electrode material or the aforementioned method of making the electrode material have a wide potential window in supercapacitor energy storage materials; the electrode material with a wide potential window can significantly improve the energy density of the device.

[0018] In the above technical solution, further, the heterojunction electrode material is used as the positive electrode of the supercapacitor and is assembled with other negative electrode materials into an asymmetric supercapacitor.

[0019] The present invention uses microwave effect through microwave assisted hydrothermal process to regulate the crystal structure of heterojunction electrode materials, such as generating lattice expansion, oxygen vacancies, adjusting the preferred orientation of crystal planes, optimizing the microscopic morphology of products, such as generating nanowire morphology formed by stacking nanoparticles, generating hierarchical pore structure, rough surface, etc., tuning the interface electronic structure, such as generating built-in electric field and other characteristics, and then synthesizing heterojunction composite electrode materials with high hydroxyl affinity. The heterojunction composite electrode materials with high hydroxyl affinity significantly improve the electrode window.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] Different from the current electrolyte modification to broaden the stable electrochemical window of the electrode, the present invention proposes to use microwave-assisted process heterojunction electrode construction design from the perspective of electrode material design optimization, and use microwave effect to achieve the regulation of the microstructural characteristics of the electrode material, and develop heterojunction composite electrode materials with strong hydroxyl affinity, so as to achieve the purpose of greatly broadening the electrode potential window. The present invention does not adopt electrolyte modification measures, and also avoids the problems of increased viscosity and slow kinetics existing in electrolyte modification.

[0022] The strong hydroxyl-affinity heterojunction material of the present invention can improve the electrode potential window, which is not achieved or reported in current related research. For existing heterojunctions or other conventional supercapacitor materials, transition metal inorganic compounds (oxides, carbon oxides, hydroxides, sulfides, etc.), if conventional aqueous electrolytes are used (the voltage limit of decomposition is 1.23V), the potential window of single electrode materials under a three-electrode test system is generally less than 0.8 V, and is often concentrated around 0.6 V. The strong hydroxyl-affinity heterojunction material of the present invention has a stable potential window greater than 0.8 V under conventional electrolytes, and can be as high as 1.23 V close to the water decomposition potential; as given in the embodiment, the MnCO3 / NiO heterojunction potential window is 1 V; the Co3O4@LaF3 heterojunction potential window is 1.1 V; the CoCo2O4@NiMn2O4 heterojunction potential window can reach 1.2 V, which is close to the limit of electrolyte decomposition. Devices assembled using highly hydroxyl-affinity heterojunction materials as supercapacitor electrode materials have higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Microwave-assisted preparation of CoCo2O4@NiMn2O4 heterojunction XRD pattern;

[0024] Figure 2 TEM image of microwave-assisted prepared CoCo2O4@NiMn2O4 heterojunction and related selected area electron diffraction pattern; (a) scale bar 200nm, (b) scale bar 50nm, (c) HRTEM image, (d) SAED image;

[0025] Figure 3 Microwave-assisted preparation of CoCo2O4@NiMn2O4 heterojunction OH - Adsorption energy calculation results;

[0026] Figure 4 Comparison of charge and discharge curves of microwave-assisted prepared CoCo2O4@NiMn2O4 heterojunction and single CoCo2O4 and NiMn2O4 electrodes;

[0027] Figure 5 XRD pattern of microwave-assisted preparation of MnCO3 / NiO heterojunction;

[0028] Figure 6 SEM image of microwave-assisted preparation of MnCO3 / NiO heterojunction;

[0029] Figure 7 Cyclic voltammogram of microwave-assisted prepared MnCO3 / NiO heterojunction;

[0030] Figure 8 Microwave-assisted preparation of Co3O4 / LaF3 heterojunction XRD patterns;

[0031] Fig. 9 SEM image of Co3O4 / LaF3 heterojunction prepared by microwave-assisted method;

[0032] Fig.10 Comparison of cyclic voltammetry curves of microwave-assisted prepared Co3O4 / LaF3 heterojunction and single Co3O4 electrode. DETAILED DESCRIPTION

[0033] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0034] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0035] Example 1

[0036] The chemicals used in this example are: nickel foam, cobalt nitrate, nickel nitrate, potassium permanganate, ammonium fluoride, urea, 3M HCl, acetone, anhydrous ethanol, and deionized water. The preparation steps are as follows:

[0037] 1) Cut the nickel foam into the desired shape, such as strips or circles, and place them in HCl, acetone, anhydrous ethanol, and deionized water for ultrasonic immersion cleaning to remove surface dirt and oxides, which is beneficial to the subsequent microwave-assisted growth and attachment of hydrothermal active substances.

[0038] 2) 0.75 mmol of cobalt nitrate hexahydrate, 0.97 mmol of ammonium fluoride and 3 mmol of urea were fully mixed and soaked in nickel foam, which was placed in a microwave high-pressure reactor and heated to 140°C at 800 W for 1 hour. Before the microwave temperature reached 100°C, it was heated at a rate of 8°C / min. After heating to 100°C, it was kept warm for 5 minutes, and then reached 140°C at 5°C / min. Subsequently, the reacted nickel foam was washed and dried, placed in a tube furnace, and sintered at 400°C for 2 hours in an air atmosphere to obtain CoCo2O4 nanowires with abundant surface pores.

[0039] 3) The nickel foam obtained in step 2) is further immersed in a uniform aqueous solution containing 0.66 mmol potassium permanganate, 0.33 mmol nickel nitrate hexahydrate, 2 mmol ammonium fluoride and 5 mmol urea for 30 min.

[0040] 4) The mixed solution and the soaked nickel foam in step 3) were transferred to a microwave autoclave and heated to 160°C at 800 W for 1 h. Before the microwave temperature reached 100°C, it was heated at a rate of 10°C / min. After heating to 100°C, it was kept warm for 5 min, and then reached 160°C at a rate of 5°C / min.

[0041] 5) After washing and drying, the nickel foam after the reaction is further placed in a tube furnace and sintered at 450° C. for 2 h under a nitrogen protective atmosphere to obtain a CoCo2O4@NiMn2O4 heterojunction composite electrode material with strong hydroxyl affinity.

[0042] Figure 1 The XRD spectrum of the microwave-assisted preparation of CoCo2O4@NiMn2O4 heterojunction. It can be clearly seen from the figure that a high-purity CoCo2O4 product was obtained after the first microwave-assisted hydrothermal process. Further, the obtained CoCo2O4 was used as the substrate, and a high-purity NiMn2O4 product was synthesized on the basis of CoCo2O4 after a secondary microwave-assisted hydrothermal process. From the XRD results, it can be clearly seen that the CoCo2O4@NiMn2O4 heterojunction composite electrode material was obtained by microwave-assisted hydrothermal process.

[0043] Figure 2 TEM image and related selected area electron diffraction pattern of CoCo2O4@NiMn2O4 heterojunction prepared by microwave assisted method. Figure 2 (a) and Figure 2 In (b), it can be found that the prepared heterojunction composite material presents a hierarchical composite morphology of surface NiMn2O4 nanosheets and inner CoCo2O4 nanowires. Figure 2 (c) The HRTEM image clearly shows the interface, with clear lattice fringes on both sides. The interplanar spacings of 0.247 and 0.297 nm on both sides of the marked line can be attributed to the (311) plane of CoCo2O4 (PDF#80-1533) and the (220) plane of NiMn2O4 (PDF#01-1110), respectively, verifying the successful construction of the CoCo2O4-NiMn2O4 interface. Figure 2 (d) SAED pattern further reveals two sets of alternating diffraction rings on the (111), (220) planes of CoCo2O4 (PDF#80-1533) and the (220), (311), (400) planes of NiMn2O4 (PDF#01-1110), indicating that the CoCo2O4@NiMn2O4 heterojunction was successfully constructed.

[0044] Figure 3 Microwave-assisted preparation of CoCo2O4@NiMn2O4 heterojunction OH - Adsorption energy calculation results. Compared with single component CoCo2O4 (-0.788 eV) and NiMn2O4 (-0.855 eV), the OH of CoCo2O4@NiMn2O4 synthesized by microwave effect is - The adsorption energy is significantly reduced to -3.05 eV, showing that the adsorption of OH - Strong affinity, that is, strong affinity for hydroxide.

[0045] Figure 4 Comparison results of charge and discharge curves of microwave-assisted prepared CoCo2O4@NiMn2O4 heterojunction and single CoCo2O4 and NiMn2O4 electrodes. Compared with CoCo2O4 and NiMn2O4 electrodes, the charge and discharge time of CoCo2O4@NiMn2O4 heterojunction is significantly prolonged and the potential window is enlarged, indicating that its storage capacity (C) and electrochemical stability window (V) are significantly enhanced, indicating that the strong hydroxyl-philic heterojunction integrated to improve the potential window and specific capacity of the electrode. The prepared CoCo2O4@NiMn2O4 heterojunction shows an expanded potential window of 1.2 V close to the water decomposition limit (in a three-electrode system of 6 M KOH, platinum mesh is the counter electrode, saturated calomel electrode is the reference electrode, and CoCo2O4@NiMn2O4 is the working electrode) and high specific capacity (1 A g -1 2065.2 C g-1 ).

[0046] Example 2

[0047] The drugs used in this example are: manganese acetate, nickel nitrate, sodium citrate, urea, anhydrous ethanol, and deionized water. The preparation steps are as follows:

[0048] 1) Accurately weigh 0.4 mmol manganese acetate tetrahydrate, 0.4 mmol nickel nitrate hexahydrate, 0.2 mmol urea, and 0.12 mmol sodium citrate, prepare a 40 mL aqueous solution, and stir magnetically for 0.5 h to form a homogeneous solution.

[0049] 2) The homogeneous solution was placed in a microwave autoclave and kept at 140°C for 45 min at 800 W. Before the microwave temperature reached 100°C, it was heated at a rate of 8°C / min. After heating to 100°C, it was kept for 5 min, and then reached 140°C at a rate of 6°C / min.

[0050] 3) After cooling naturally to room temperature, the reactant was taken out and washed with deionized water and ethanol several times, and then dried at 70 °C for 8 h to obtain a precursor. The precursor was then kept at 300 °C in a tube furnace under an argon atmosphere for 2 h to obtain a strongly hydroxyl-philic MnCO3 / NiO heterojunction nanocomposite material. In addition, the same method was used to prepare pure NiO powder without adding manganese acetate tetrahydrate, and pure MnCO3 powder was prepared without adding nickel nitrate hexahydrate and annealing process.

[0051] Figure 5 XRD spectrum of microwave-assisted preparation of MnCO3 / NiO heterojunction. It can be found that compared with pure phases of MnCO3 (PDF#86-0173) and NiO (PDF#89-7130), the composite product obtained by microwave-assisted hydrothermal process is a composite phase of the two, and there is no other impure phase. Figure 6 This is a SEM image of a microwave-assisted preparation of a MnCO3 / NiO heterojunction. It can be clearly seen from the figure that the heterojunction obtained by the microwave-assisted hydrothermal process presents a hierarchical composite morphology of nanosheet flower balls and composite nanoparticles. Further first-principles theoretical calculations show that the adsorption energy of the obtained MnCO3 / NiO heterojunction is -4.58eV, which has strong hydroxyl affinity.

[0052] Figure 7 The cyclic voltammogram of the microwave-assisted preparation of the MnCO3 / NiO heterojunction. It can be found that under the traditional three-electrode system, the obtained strong hydroxyl-philic heterojunction material shows a 1.0 V stable electrochemical window and a large cyclic voltammogram integral area, indicating that the obtained heterojunction shows a significantly broadened potential window and specific capacity.

[0053] Example 3

[0054] The chemicals used in this example are: nickel foam, cobalt nitrate, lanthanum nitrate, ammonium fluoride, urea, anhydrous ethanol, and deionized water. The preparation steps are as follows:

[0055] 1) Cut the nickel foam into the desired shape, such as strips or circles, and place them in HCl, acetone, anhydrous ethanol, and deionized water for ultrasonic immersion cleaning to remove surface dirt and oxides, which is beneficial to the subsequent growth and attachment of microwave-assisted hydrothermal active substances.

[0056] 2) Weigh 1 mmol of cobalt nitrate, 0.75 mmol of lanthanum nitrate, 2 mmol of ammonium fluoride, and 6 mmol of urea, and add deionized water to prepare a 30 ml uniform solution. Soak the treated nickel foam in the above solution for 30 min.

[0057] 3) The nickel foam soaked in the above solution was placed in a microwave hydrothermal reactor and kept at 140 °C for 90 min at a power of 900 W. Before the microwave temperature reached 100 °C, it was heated at a rate of 10 °C / min. After heating to 100 °C, it was kept for 5 min, and then reached 140 °C at a rate of 5 °C / min.

[0058] 4) The nickel foam (i.e., Co3O4 / LaF3 precursor) obtained in step 3) is washed, dried, placed in a tube furnace under air atmosphere, heated to 400°C and kept warm for 3 h to obtain Co3O4 / LaF3@NF heterojunction material.

[0059] Figure 8 The XRD spectrum of the microwave-assisted preparation of Co3O4 / LaF3 heterojunction is shown. As shown in the figure, for the single Co3O4 sample, the strong diffraction peaks that appear can well correspond to the crystal planes (111), (220), (311), (222), (400), (422), (511), (440), (533) and (444) of Co3O4 (JCPDS#73-1701), indicating that the synthesized pure phase Co3O4. When the corresponding lanthanum source is added, the diffraction peaks of the obtained product, in addition to the above-mentioned Co3O4 (JCPDS#73-1701) corresponding crystal planes, also appear a complete set of LaF3 (JCPDS#77-2029) diffraction crystal planes, indicating that the method provided by the present invention successfully prepares the Co3O4 composite LaF3 heterojunction material.

[0060] Fig. 9This is a SEM image of the microwave-assisted preparation of Co3O4 / LaF3 heterojunction. It can be found that the obtained heterojunction material presents a hierarchical microstructure of nanoparticles attached to nanosheets-nanowires, showing a 2D-1D / 0D multi-level hierarchical structure. There are abundant void spaces between the fluffy distributed nanosheets and nanowires, which can effectively shorten the transmission distance of electrons and ions and buffer the volume change of the composite material during the charge and discharge process. The finely dispersed nanoparticles attached and distributed on the nanosheet-nanowire skeleton can effectively enhance the material utilization rate and facilitate the acquisition of higher volume energy density. Further first-principles theoretical calculations show that the adsorption energy of the obtained Co3O4 / LaF3 heterojunction is -3.27 eV, which has strong hydroxyl affinity.

[0061] Fig.10 Comparison results of cyclic voltammetry curves of microwave-assisted prepared Co3O4 / LaF3 heterojunction and single Co3O4 electrode. Compared with the 0.8 V (0.8 V, 0~0.8 V vs. SCE) potential window of single Co3O4 electrode, the constructed strong hydroxyl-philic Co3O4 / LaF3 heterojunction presents a high working potential of 1.1 V (0~1.1 V vs. SCE) under the traditional three-electrode test system. At the same time, compared with the single Co3O4 electrode, the larger CV curve integral area of ​​the Co3O4 / LaF3 heterojunction proves its higher storage capacity. The above results effectively prove the effectiveness of microwave-assisted construction of strong hydroxyl-philic heterojunction composite materials in integrated expansion of potential window and specific capacity.

[0062] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A strongly hydroxyl-affinity heterojunction electrode material with a wide potential window, characterized in that: The heterojunction electrode material is prepared by a microwave-assisted hydrothermal process and has strong affinity for hydroxyl radicals; the potential window of the heterojunction electrode material is greater than 0.8 V in a conventional aqueous electrolyte three-electrode test system; The heterogeneous components in the heterojunction electrode material are all transition metal inorganic compounds; The heterojunction electrode material is composited by two heterogeneous components, both of which are transition metal inorganic compounds; the transition metal inorganic compound is a non-noble transition metal oxide, carbon oxide, hydroxide, sulfide or lanthanide metal fluoride; The OH of the heterojunction electrode material - Adsorption energy <-3eV.

2. The heterojunction electrode material according to claim 1, characterized in that: The non-precious transition metal oxides include CuO, Fe3O4, Co3O4 or NiMn2O4; the non-precious transition metal carbon oxides include MnCO3; the non-precious transition metal hydroxides include layered double hydroxides; the non-precious transition metal sulfides include CuS and MoS2; and the lanthanide metal fluorides include LaF3.

3. The heterojunction electrode material according to claim 1, characterized in that: The heterojunction electrode material is CoCo2O4@NiMn2O4, MnCO3 / NiO or Co3O4 / LaF3.

4. The heterojunction electrode material according to claim 1, characterized in that: The microwave-assisted hydrothermal process includes: treating the raw material solution of heterogeneous components with microwaves, with a microwave power of 800-1100 W, heating to a target temperature of 120-150°C, and a microwave treatment time of 1-3 h; heating at a rate of 10-12°C / min before the microwave heating temperature reaches 100°C, and after heating to 100°C, keeping the temperature for 5 min, and then reaching the target temperature at a rate of 5-8°C / min.

5. A method for making an electrode material have a wide potential window, characterized in that: The method uses a microwave-assisted hydrothermal process to prepare a heterojunction electrode material, so that the heterojunction electrode material has a strong affinity for hydroxyl radicals, OH - Adsorption energy < -3eV; The heterojunction electrode material is a composite of two heterogeneous components of non-noble transition metal oxides, carbon oxides, hydroxides, sulfides or lanthanide metal fluorides; The microwave-assisted hydrothermal process comprises: treating the raw material solution of heterogeneous components with microwaves, the microwave power is 800-1100 W, the temperature is raised to 120-150° C., and the microwave treatment time is 1-3 h.

6. Use of the heterojunction electrode material according to any one of claims 1 to 4 or the method according to claim 5 in supercapacitor energy storage materials.

Citation Information

Patent Citations

  • Preparation of Al-doped MnO2 electrode material and construction of wide voltage window flexible super electric device

    CN113470987A

  • Preparation and application of conductive polymer-tungsten trioxide dehydrate / tungsten self-supporting electrode with wide voltage window

    CN115240993A

  • Wide-voltage-window aqueous electrolyte for forming SEI film based on physical process and preparation method and application of wide-voltage-window aqueous electrolyte

    CN115376838A

  • Construction method of wide voltage window zinc ion flexible hybrid supercapacitor

    CN115863063A

  • Low-temperature-resistant high-voltage aqueous electrolyte, preparation method thereof and application of low-temperature-resistant high-voltage aqueous electrolyte in miniature supercapacitor

    CN116266506A